Leksikaliserte ordsamband i norsk - Grønvik, Oddrun (Nordiske Studier i Leksikografi, 2010)
What is the inventory of Norwegian phraseology, and how can one best capture and describe it? This task has been a challenge for the editors of Norsk Ordbok from 1946 onwards, both in terms of analysis and in terms of structural management. In 2003, when Norsk Ordbok 2014 launched a new digital platform for integrated management of all materials and the whole editorial process, a separate unit was created for editing fixed, grammaticalised or lexicalised phrases, and a set of general guidelines for selection and treatment were drafted. The task of sifting texts and records and editing the result is the task of the Norsk Ordbok editorial staff. In this article, at the end of the eighth out of twelve volumes, the current inventory is analysed and discussed in the light of current approaches to handling phraseology in dictionaries.